PENURUNAN JUMLAH SPERMATOSIT PAKITEN DAN SPERMATID TUBULUS SEMINIFERUS TESTIS PADA MENCIT (MUS MUSCULUS) YANG DIPAPARKAN ASAP ROKOK - SUKMANINGSIH, A.A.Sg A. (Jurnal Biologi Udayana; Vol 13 No 2 (2009): JURNAL BIOLOGI, 2009)
This study was conducted to observe the effect of cigarette smoke exposure on spermatogenesis of male mice. The animals used in this study were 63 male mice, aged 12 weeks. They were divided randomly into 3 groups, each group consisted of 21 mice. One group was used as control, two groups were used as treatment (KO = control, KM = mice group exposed by a light cigarette smoke, KJS = male exposed by a kretek cigarette smoke). The animals in each treatment were exposed by 21 cigarette smoke once daily for forty days. After 40 days of treatment, analysis on plasma level of nicotine was conducted and the testicles were sectioned and stained for qualitative and quantitative microscopic analysis. The results showed that plasma level of nicotine on the KJS group outweighed significantly (P< 0,05) the KM group. It was also found that the number of pachytent spermatocyt and spermatids for both KM and KJS cigarette smoke exposure reduced significantly (P < 0.05)
Keywords: Cigarette smoke, plasma level of nicotine, pachytent spermatocyt, spermatids